Global Pedagogy and the Question of Palestine: A Dialogue - Herrera, Linda; Peters, Michael A. (Critical Education, 2025)
Global pedagogy refers to a broad, ethically grounded approach to education that extends beyond national boundaries and emphasizes the collective responsibility to teach and learn about interconnected global crises and historical injustices. The question of Palestine and the ongoing genocide in Gaza serve as the "canary in the coalmine". Its suppression is not an isolated phenomenon but a diagnostic for a wider authoritarian turn that seeks to foreclose the very possibility of critical, transnational solidarity. In this dialogue, Michel Peters, a philosopher of education, and Linda Herrera, a critical anthropologist of education in the Middle East, engage in a dialogue about how educators can keep critical thought and solidarity alive by partaking in practices that are resilient, resourceful, and relentlessly focused on building counter-publics. These requires embracing a “fugitive” pedagogy, curating and archiving counter-memories, and building transnational literacies of solidarity.